OPTIMASI MESIN PERAJANG SINGKONG DENGAN MEKANISME PENDORONG BAHAN BAKU OTOMATIS - Altruis Krisman Runesi; Daud P. Mangesa; Rima Nindia Selan (Universitas Nusa Cendana, 2025)
ABSTRACT Cassava is one of the agricultural commodities spread across most parts of Indonesia, especially in the province of NTT. The abundant potential makes cassava a staple food for the people of East Nusa Tenggara. UD. ML is a company that produces and markets cassava chips to meet the needs of the people of Kupang and its surroundings. During the cassava chips production process, the tools used are still using manual choppers with human power, so that it can cause defective products to be produced, such as errors in cutting that are not too thin or thick and the pieces are destroyed because they are too thin and worker fatigue when chopping cassava . The research method used in this study is the experimental method, observation and literature study. From the test results, it was found that the chopping capacity at blade setting A was 660 grams, knife B was 740 grams, and knife C was 800 grams, with a thickness of 1-3mm.